A New Technique Called Annotation Used To Categories The Content Of Web Pages (International Journal of Engineering and Computer Science, 2014)
Now-a-days   databases        become   web accessible; these  databases having data units are encoded.  To separate data units assign   meaningful labels.  To  assign  labels  there  is an   automatic  annotation  approach  which  automatically  assign  labels  to  data units within  the  search  result  records  returned  from  web  databases. For that it    provides  an  annotation  wrapper  for  the  search  site  to   automatically  constructed   and  annotate   the  new  result   pages  from  the  same  web  databases. There  are  six   basic  annotators, for  every  basic  annotator  we produce  label   for   the  data  units  within   their  group. A  probability  model  is  selected  to determine  the  most   appropriate  label  for  each  group. This  annotation  wrapper   generate  an   annotation  rule  that  describes  how  to  extract  the  data   units  from  result   page .Once   the   annotation  wrapper  annotate  the  data  there  is  unnecessary  to   perform  the  alignment  and  annotation  phases  again. We construct an annotation  wrapper by  using  data  types,  data  contents,  presentation   styles  and  adjacency  information. In  this  paper the  data  annotation   problem  is studied  and   proposed  a  multiannotator   approach  to  automatically  constructing  an   annotation  wrapper  for   annotating  the  search  result  records  recover  from   any  given  web  databases.